Waypoint Navigation of AR.Drone Quadrotor Using Fuzzy Logic Controller - Veronica Indrawati; Agung Prayitno; Thomas Ardi Kusuma (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
In this paper, AR.Drone is flown autonomously from the initial position (x,y,z) to the desired position called waypoint (xdes,ydes,zdes) using Fuzzy Logic Controller (FLC). The FLC consists of three control loops which are pitch control loop, roll control loop and vertical rate control loop. Pitch control loop is used to control the x-position of the AR.Drone; the inputs are the desired x-position and current value of x-position, while its output is the pitch.  Roll control loop is used to control the y-position of the AR.Drone; the inputs are the desired y-position and current value of y-position, while its output is the roll. Vertical rate control loop is used to control the z-position of the AR.Drone; the inputs are the desired z-position and current value of z-position and its output is the vertical rate. The algorithm is realized in three flight schemes and the navigation data is recorded. The first flight scheme: a desired x-position, xdes, of AR.Drone will be reached first followed by a desired y-position, ydes, and lastly a desired z-position, zdes.  The second flight scheme: a desired x-position and y-position, (xdes,ydes), will be reached simultaneously followed by a desired z-position, zdes. The third flight scheme: AR.Drone flies towards to desired position (xdes,ydes,zdes) simultaneously. The results show that the AR.Drone can reach the waypoint with the three schemes well. However, the flight scheme straight towards the waypoint with the FLC working simultaneously is the most satisfying one.